Avaliação dos mecanismos de ação envolvidos na atividade antiulcerogênica de Serjania marginata frente á doença ulcerosa péptica experimental - Périco, Larissa Lucena [UNESP] (2014)
Peptic ulcer disease includes both gastric and duodenal ulcers and has been a major threat to the world’s population over the past two centuries. The complex and multifactorial pathogenesis of this disease occurs due to an imbalance between aggressive (hydrochloric acid, pepsin, ethanol, NSAIDs, stress, Helicobacter pylori, among others) and protective factors (mucus, bicarbonate, prostaglandins, blood flow) of the mucosa of stomach or duodenum. In an attempt to protect the gastric mucosa from hydrochloric acid, improve ulcer healing and prevent recurrence, the pharmacological control of acid secretion has long represented an aim of antiulcerogenic drugs. Among the options available in the market, we have the H2 receptor antagonists and proton pump inhibitors. Some of these drugs can promote not only a range of side effects, but also a decrease in effectiveness in the treatment of ulcers and primarily not prevent its recurrence. Thus, the necessity of more effective and safe agents is clearly pressing. Hence, scientific efforts are conduct to find the adequate treatment from natural products, such as source of drugs. Serjania marginata Casar., a specie commonly found in the Brazilian Cerrado, has been described by its popular indication to treat stomach aches, however, there are no studies on their pharmacological activities for the treatment or prevention of peptic ulcers. Therefore, the aim of this study was to evaluate the gastroprotective activity of the hydroalcoholic extract from leaves of Serjania marginata (EHSM) in different experimental models. It was initially performed a test of acute toxicity and motor performance to evaluate the possible toxicity and neurotoxic effects of the extract, however this did not cause any changes in these experimental models, thus demonstrating the safety of use for continuing studies with this species. It was observed that EHSM, orally administered, has a protective action against the gastric ...